Determination of the transition Point from Open Pit to Underground Mining - Chung, J.; Asad, Mohammad; Topal, Erkan; Ghosh, Apurna (2016)
Many open pit (OP) mines with considerable vertical extent are approaching towards the end of their life-of-mine (LOM), and some of them are seeking the opportunity to make the transition from OP to underground (UG) mining. While conventionally, the transition to UG mining is considered near or after the exhaustion of reserves within the ultimate pit, the decision on the best location for transition from OP to UG mining should be addressed at the strategic mine planning stage. However, defining the best location for the transition through conventional approach may not be an optimal option to explore, if UG is evident and exclusively viable from the inception. This clearly establishes the need for a mathematical model that aims to maximise the project value and considers OP and UG mining with crown pillar (CP) requirement simultaneously. Also, underground mine layout varies from one UG mining method to the other, and consequently the variation in the location of transition is eminent. Thus, focus on the selection of UG mining method must be a part of this analysis This paper presents an implementation of an integer programming (IP) based mathematical model that evaluates the changes in mining layout and the project value under possible variations in the transition point from OP to UG mining for sublevel stoping and block caving methods. The outcomes of the implementation reflect that mining strategies with OP transition to sublevel stoping and block caving methods generate higher value than OP only mining strategy. The case study not only demonstrates the difference in mining layout for both sublevel stoping method and block caving method, but also reflects that a joint consideration of OP mining, UG mining and CP placement helps to achieve maximum project value and resource utilisation.